Current and future management of the young child with early onset wheezing. Issue 2 (April 2017) - Burbank, Allison J.; Szefler, Stanley J.
Abstract : Purpose of review: In this review, we discuss current thinking in relation to available guidelines for the care of preschool-aged children with recurrent wheezing, while highlighting the gaps in our knowledge and discussing changes that could occur over the next 5 years. Recent findings: The Asthma Predictive Index as well as allergen-specific IgE, peripheral eosinophil count and exhaled nitric oxide are perhaps underutilized sources of information that can assist in predicting progression to asthma and response to therapies. Inhaled corticosteroids and leukotriene receptor antagonists decrease impairment and exacerbation frequency in wheezing children but are not disease modifying. Macrolides may be useful during acute wheezing episodes for preventing progression to more severe symptoms. Monoclonal antibodies targeting IgE and TH 2 cytokines have been successful in trials of adults and older children with asthma, but trials in younger children are needed. Summary: Establishing the phenotype and endotype of young wheezing children can be useful for prognostication of future asthma risk as well as for selection of the most appropriate treatment. Primary asthma prevention strategies are needed during the critical developmental window in early life prior to the onset of irrecoverable loss of lung function.